Prevalensi Bakteri Methicillin-Resistant Staphylococcus aureus (MRSA) Pada Peralatan Laboratorium - kurniawan Kurniawan -; Eva Adaning Tyas; Supriyadi - (Universitas Muhammadiyah Surabaya, 2021)
Staphylococcus aureus bacteria are common flora bacteria that are both commensal and opportunistic pathogens in humans. They are commonly treated with antibiotics, which can lead to bacterial resistance, such as the emergence of Methicillin-Resistant Staphylococcus aureus (MRSA) bacteria, which are resistant to the β -lactam antibiotics that are currently widespread to a variety of communities, such as the campus community, which is equipped with several facilities such as laboratories. The microbiology laboratory is a practicum and research laboratory that uses materials in the form of microorganisms, hence it has the potential to transmit MRSA bacteria. The aim of this study is to find out if MRSA bacteria are present on microbiology lab equipment and how prevalent they are. This study used observational research with a descriptive research design and a purposive sampling strategy. The results of bacterial isolation on MSA medium from fourteen laboratory equipment revealed that thirteen devices exhibited bacterial growth, whereas one device had none. Seven bacterial isolates with S. aureus-like features are detected growing in three of the thirteen equipment, the LAF, incubator, and manual autoclave. The seven bacterial isolates were identified as having round colony shape, glistening, opaque, convex yellow pigmentation, round cell morphology, clustered like grapes and purple in color, positive for coagulase and catalase, and resistance to methicillin antibiotics (MRSA bacteria). It can be concluded that of the fourteen-laboratory equipment examined, three instruments, namely the LAF, incubator, and manual autoclave, were found to be overgrown with MRSA bacteria, with the prevalence of MRSA bacteria in microbiology laboratory equipment reaching 21.4%. Keywords: laboratory equipment, MRSA, prevalence, S. aureus